2008
DOI: 10.1002/mame.200700204
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Properties of Polyethylene/Clay Nanocomposite Drawn Fibers

Abstract: The influence of an elongational flow on the morphology of PE/clay nanocomposite drawn fibers was studied. An increase of the elastic modulus and the tensile strength as well as a decrease of the elongation at break are observed with increasing draw ratio. The applied elongational gradient orients the polymer chains and the clay particles along the spinning direction. When the applied flow results in the formation and the orientation of exfoliated nanoparticles, a pronounced increase of the mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 25 publications
8
42
0
Order By: Relevance
“…These results are in good agreement with the conclusions reported by La Mantia et al [30]. Therefore, the experienced increase of the mechanical properties due to nanosilica introduction cannot be attributed to different chain orientation in the tested materials.…”
Section: Microstructuresupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in good agreement with the conclusions reported by La Mantia et al [30]. Therefore, the experienced increase of the mechanical properties due to nanosilica introduction cannot be attributed to different chain orientation in the tested materials.…”
Section: Microstructuresupporting
confidence: 93%
“…Also Ruan et al [32] reported that the addition of MWCNT at a concentration of 5 wt% had a nucleating effects on polyethylene crystals, particularly in the highly aligned fibers, but the crystallinity of the composite fibers was slightly lower than that of the pristine fibers. On the other hand, La Mantia et al [30] found that organomodified layered silicates did not have any effect on the crystallization properties of LLDPE fibers and hypothesized that the orientation in both crystalline and amorphous phases were similar for filled and unfilled fibers. According to our previous works on polyethylene based nanocomposites [20,21,23], we can hypothesize that the limited influence played by fumed silica nanoparticles on the crystallization properties of our HDPE matrix could be probably ascribed to their dispersion state.…”
Section: Results and Discussion 31 Dsc And Dmta Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that even in the case of low molecular weight polymers, the presence of nanofiller and sometimes the lower level of chain extension determine the formation of various type of defects, and hence relatively low modulus and strength values of the spun fibers. In the case of polyethylene fibers, both linear low density and high density polymers at very low melt flow, between 0.27 and 0.9 dg/min (190°C, 2.16 kg), were spun with various organo-modified clays or with fumed silica [14][15][16][17][18]. The high molecular weight of polymers allowed an efficient drawing process and the achievement of higher mechanical properties of drawn nanocomposite fiber with respect to those of neat polymer.…”
Section: Introductionmentioning
confidence: 99%